Bioelectro-Claus processes using MFC technology: Influence of co-substrate. (August 2015) - Raschitor, A.; Soreanu, G.; Fernandez-Marchante, C.M.; Lobato, J.; Cañizares, P.; Cretescu, I.; Rodrigo, M.A.
Highlights: Sulphide can be efficiently removed from wastewater using microbial fuel cell. Maximum power density of 150 mW m −2 can be attained. COD is removed simultaneously with sulphide oxidation. Co-substrate influences on speciation and rate but not on electricity production. Abstract: This work is focused on the removal of sulphide from wastewater using a two chamber microbial fuel cell, seeded with activated sludge and operated in semi-continuous mode. Two co-substrates were used in order to provide the system for carbon and nutrient source: actual urban wastewater and synthetic wastewater. Results show that sulphide is efficiency depleted (removals over 94%) and that electricity is efficiently produced (maximum power density is 150 mW m −2 ) meanwhile COD is also oxidised (removals higher than 60%). Sulphur and sulphate are obtained as the final products of the oxidation and final speciation depends on the type of co-substrate used. The start-up of the system is very rapid and production of electricity and polarisation curves do not depend on the co-substrate.